Morbidity due to External Causes among youngsters in an area of the municipality of Porto Alegre-RS - Marta Cocco; Marta Julia Marques Lopes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This study aims at learning and understanding the morbidity due to External Causes among youngsters, considering the demand for health care services in the Area of Lomba do Pinheiro and Partenon in the municipality of Porto Alegre - RS over the time frame between 2002 and 2005. The intention is discussing situations of vulnerability regarding age group, gender relations and community life experience, among others. It is a hybrid descriptive epidemiological study of the ecologic type aggregated to a time series with elements of qualitative collection and analysis. The research constitutes a Master Paper Project from the Nursing Post-Graduation Program of the Nursing School of the Federal University of Rio Grande do Sul.